7 - Disputas de e por espaços político-identitários: o rap e os movimentos sociais em Cabo Verde - Lima, Redy Wilson; Robalo, Alexssandro (Africa Development, 2024)
Independent since 1975 and democratic since 1991, Cabo Verde has not escaped the waves of urban protests that plagued African capitals in the second half of the 2000s. Rap, perceived as the new expression of protest by urban youth, consolidates itself in the 2000s as one of the main actors in the Cape Verdean political scene and becomes an important vehicle for mobilizing and building an urban culture of resistance, amplifying these issues. This article, based on an ethnographic research in the cities of Praia (Santiago Island) and Mindelo (São Vicente Island), seeks to answer three questions: on how rap has shown the identity, social and urban contradictions; how it has articulated with other types of social movements; 3) what is the place of women in rap and street politics?